Trade Credit Contracts - Klapper, Leora; Laeven, Luc; Rajan, Raghuram (2012)
This paper provides new evidence on the unique role of trade credit and contracting terms as a way for both sellers and buyers to mange business risk. The authors use a novel and unique dataset on almost 30,000 supplier contracts for 56 large buyers and more than 24,000 suppliers in Europe and North America. The sample of buyers and suppliers includes firms of varying size, investment grade, and sectors. The paper finds evidence in support of four important, and not mutually exclusive, reasons for trade credit: 1) as a method of financing; 2) as a means of price discrimination; 3) as a bond assuring buyers of product quality; and 4) as a screening mechanism to gauge buyer default risk. In particular, the analysis finds that the largest and most creditworthy buyers receive contracts with the longest maturities, as measured by net days, from smaller, investment grade suppliers. In comparison, early payment discounts seem to be used as a risk management tool to limit the potential nonpayment risk of trade credit. Early payment discounts are generally offered to smaller, non-investment grade buyers. The results suggest that contract terms are jointly determined by supplier and buyer characteristics.